OrchFlow: uma arquitetura para orquestração de redes OpenFlow com múltiplos controladores - Frate, Marcelo (Universidade Federal de São Carlos, 2017)
Since the emergence of the Software-Defined Networking (SDN), and, more precisely, since the development of an open interface in 2008 called OpenFlow protocol, it is being observed that this new networking paradigm is deeply remodeling the IP-protocol- based networks. It means that new mechanisms of provision services are being possible, which ensures scalability and reduces costs. Although this new paradigm has been created to centralize the control logic, there is the possibility of decentralizing it through the parceling of control tasks between two or more controllers. In this scenario, the subdivision of administrative domain in smaller subdomains in order to have each of them being controlled by one single controller has been an alternative to ensure scalability in SDN. The OpenFlow protocol allows communication among switches and controllers to another controller. However, the protocol does not define how this communication between one controller to other should be done. It is mandatory, therefore, the development of protocol independent solutions able to distribute this logic inside the same administrative domain. New proposals have been arisen, but their applications either use equal controllers or demand the development of new controllers specifically designed. This master’s research aims to offer the fundamentals to the development of an architecture here so called Orch Flow, able to receive application demands and organize them in a way it provides requested services through an OpenFlow network designed with two or more different implementation controllers. The OrchFlow architecture that is being proposed accomplishes its task through handling multiple OpenFlow controllers hierarchically and providing network access through three distinct modes: Proactive, Reactive and Hybrid.
OrchFlow: an architecture for orchestration of OpenFlow networks with multiple controllers
Keywords: TCP/IP (Protocolo de rede de computador); Arquitetura de computador; Computer architecture; TCP/IP (Computer network protocol); SDN - Software-Defined Networking; OpenFlow; OrchFlow; Orquestração; Múltiplos Controladores; Orquestration; Multiple controllers; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO